Characterisation of the crack tip plastic zone in fatigue via synchrotron X-ray diffraction - Carrera, Manuel; Sánchez-Cruces, Manuel Alejandro; Kelleher, Joseph F.; Tai, Yee-Han; Yates, John R.; Withers, Philip J.; López-Crespo, Pablo (Wiley, 2022)
This paper describes a new methodology for characterising the plastic zoneahead of a fatigue crack. This methodology is applied to a set of experimentaldata obtained by synchrotron X-ray diffraction on a bainitic steel compact ten-sion specimen. The methodology is based on generating the equivalent VonMises strain field from the X-ray experimental elastic strain maps. Based onthe material response, a threshold is then applied on the equivalent strainmaps to identify the size and shape of the plastic zone. The experimental plas-tic zone lies between the plane strain and plane stress Westergaard's boundsbut closer to the plane strain theoretical prediction confirming that the volumeanalyzed is predominantly subjected to plane strain conditions. However, theobserved plastic zone has a somewhat flatter shape, extending further from thecrack plane but less extended in the crack growing direction.
Keywords: Plásticos; Bainitic steel; Fatigue plastic zone; Synchrotron X-ray diffraction